2003
DOI: 10.1093/rheumatology/keg315
|View full text |Cite
|
Sign up to set email alerts
|

Protein interaction for an interferon-inducible systemic lupus associated gene, IFIT1

Abstract: The gene expression profile seems to be the molecular basis of the diverse immune phenotype of SLE. On the basis of the SLE-related genes found in this study, we suggest that the interferon-related immune pathway is important in the pathogenesis of SLE. IFIT1 is the first gene described as a candidate gene for SLE, and may function by activating Rho proteins through interaction with Rho/Rac guanine nucleotide exchange factor. IFIT1 and the interferon-related pathway may provide potential targets for novel inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 20 publications
1
54
0
1
Order By: Relevance
“…G1P2 has also been demonstrated to enhance the innate antiviral response via regulation of IFN-stimulated intracellular signaling pathways (64). Notably, for other genes including IFIT1, IFIT4, and IFI44, there is limited knowledge regarding their biochemical function or biological effect for the host, although it has been noted that their expression is increased in the autoimmune disease systemic lupus erythematosus (65,66). It is therefore interesting to speculate that periodontitis could exhibit an autoimmune component that may result from inefficient tissue autophagy (67).…”
Section: Discussionmentioning
confidence: 99%
“…G1P2 has also been demonstrated to enhance the innate antiviral response via regulation of IFN-stimulated intracellular signaling pathways (64). Notably, for other genes including IFIT1, IFIT4, and IFI44, there is limited knowledge regarding their biochemical function or biological effect for the host, although it has been noted that their expression is increased in the autoimmune disease systemic lupus erythematosus (65,66). It is therefore interesting to speculate that periodontitis could exhibit an autoimmune component that may result from inefficient tissue autophagy (67).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive profiling of gene expression in peripheral blood mononuclear cells (PBMCs) and protein expression in sera from patients has consistently shown the upregulation of IFN-inducible genes in SLE compared with normal controls. 10,11,13,[49][50][51][52] IFN signature in PBMCs Baechler et al 10 studied gene expression microarray profiles in 48 SLE patients and 42 controls to identify pathways that might be dysregulated in PBMCs of SLE patients. Several immune-related genes were up-regulated in the SLE patients including Fc receptor for IgA (FCAR, CD89), Fc receptor for IgG such as FcgRIIA (CD32) and FcgRI (CD64), TNFRSF6 (Fas/CD95), and three molecules in the inflammatory IL-1 cytokine pathway: IL-1b, IL-1 receptor II (IL-1RII) and IL-1 receptor antagonist.…”
Section: Expression Profiling Of Ifn-responsive Genes In Slementioning
confidence: 99%
“…53 Among these, at least nine genes (LY6E, OASL, IFIT1, IFIT4, STAT1, MX1, MX2, PLSCR1 and IRF7) were replicated by other independently carried out microarray studies. 11,[49][50][51] Baechler and co-workers 10,53 also examined whether there was any clinical feature that distinguishes 'IFNhigh' group of patients from 'IFN-low group'. The frequency of SLE who have a manifestation of renal disease, central nervous system lupus and hematological deficit (particularly leukopenia, lymphopenia and thrombocytopenia) was significantly higher in the 'IFNhigh' group of patients as compared to the 'IFN-low', suggesting that IFN signature can be a marker for patients with severe SLE.…”
Section: Expression Profiling Of Ifn-responsive Genes In Slementioning
confidence: 99%
“…Recently, OAS was rediscovered to be a part of interferon signature(s), which plays an important role in the pathogenesis of SLE by several microarray gene expression studies [47] , [48]. These studies have identified three isoforms of OAS, i.e., OAS1, OAS2, and OASL.…”
Section: ′5′-oligoadenylate Synthetasementioning
confidence: 99%